RESPON STAKEHOLDER TERHADAP KERUSAKAN HUTAN DI DESA TIRTANAGAYA KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Sukri, Moh; Golar, Golar; Massiri, Sudirman Dg (ForestSains, 2018)
Environmental degradation as indicated by the depletion of resources and the destruction of natural habitats is the impact of human-nature relationship. Furthermore, forest fires, illegal logging, gold mining and other related activities are forms of forest destruction that can be claimed to be more intense lately. Therefore, an initial measure should be carried out including identifying stakeholders’ responses toward the issues and assessment on the level of destruction. This study aims to examine stakeholders’ responses toward forest destruction in Tirtanagaya Village, Bolano Lambunu Sub-district, Parigi Moutong Regency. The techniques of data collection were observation and in-depth interview. Several key informants were selected for the interview in order to investigate their responses toward forest destruction in the study site. It used qualitative descriptive method for data analysis. In overall, the finding indicates that the responses of stakeholders in relation with forest destruction issues are relatively poor. It is evidenced by their low participation and lack of real actions to promote forest preservation. It will have a detrimental impact on the joint effort for overcoming the problems of forest destruction in Tirtanagaya Village.